PENGAKUAN HUKUM NASIONAL TERHADAP HUKUM ADAT DALAM KEPEMILIKAN DAN PENGOLAHAN TANAH - Aartje Tehupiory (Fakultas Hukum Universitas Kristen Indonesia, 2016)
In national law, the existence of recognition of customary law, over ownership and management of cus- tomary land are avowed as long as they exist. Therefore, the role of customary institutions is to provide land recommendation for each land management, for the existence and protection of Beschiking Recht and customary law society provides justice, legal certainty and legal protection for indigenous peoples. With a peculiar regulation for the needs of the people of the area, in the settlement of land disputes, it can accommodate the diversity of local customary law, which is a part of the national land law. It is recommended that the role of local government is as facilitator and coordinator in policymakers, regarding to the existence of community land, with the principle of respect for human rights and the principles of the state law. Keywords: Customary Law, Ownership and Management of Land